The simplified guide to not-for-profit accounting, formation and reporting - Scot, Laurence (John Wiley & Sons, 2010)
A complete and easy to understand guide to the fundamentals of how not-for-profit organizations are formed and run, as well as their structure and the unique accounting and reporting issues they face. Providing you with a comprehensive understanding of how to maintain the "books" of a typical nonprofit entity and comply with numerous reporting requirements, The Simplified Guide to Not-for-Profit Accounting, Formation & Reporting equips you with everything you need to know to form a Not-For-Profit, setup an accounting system, record financial transactions and report to donors and reg.